Familial Hemiplegic Migraine: A New Gene in an Italian Family - Palumbo, Pietro; Palumbo, Orazio; Operto, Francesca Felicia; Castellana, Stefano; Muro, Ester Di; Leone, Maria Pia; Biagini, Tommaso; Pastorino, Grazia; Mazza, Tommaso; Carella, Massimo; Coppola<, Giangennaro (Archives of Clinical and Medical Case Reports, 2019)
Hemiplegic migraine (HM) is a rare form of migraine characterized by severe attacks of unilateral and pulsating headache (associated with photophobia, phonophobia or nausea). To date, mutations in three different genes, ATP1A2, CACNA1A and SCN1A, are known to cause familial hemiplegic migraine (FHM) or sporadic hemiplegic migraine (SHM) phenotype, while mutations in ATP1A3 were recently associated to alternating hemiplegia of childhood (AHC). Here we report an Italian family who presented with familial hemiplegic migraine, carrier of an heterozygous ATP1A4 mutations c.1798 C>T, predicted to cause the p. (Pro600Ser) amino acid substitution, which segregated with the disease phenotype in four members. The variant, identified by using whole exome sequencing combined with Sanger sequencing, was predicted to be disease-causing by prediction software and to affect protein stability by thermodynamic study. To our knowledge, this is the first report of a mutation of ATP1A4 gene, associated to FHM, thus useful to further expand our understanding of the molecular etiology of HM. Furthermore, our evidence may suggest to consider ATP1A4 in addition to ATP1A2, ATP1A3, CACNA1A and SCN1A, in genetic screening of patients affected by HM.